Economics of grids, clouds, systems, and services : 13th International Conference, GECON 2016, Athens, Greece, September 20-22, 2016, Revised selected papers /: 13th International Conference, GECON 2016, Athens, Greece, September 20-22, 2016, Revised selected papers. (2017) - Unknown
No abstract available